Association between breakfast habits and learning concentration among elementary school students - Aniza Salzadela Pradita; Nurul Aziza; Febria Listina (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Breakfast is an important health behavior that helps meet children’s energy needs and supports cognitive function, particularly learning concentration. School-age children who regularly skip breakfast may experience inadequate glucose intake, even though glucose is the primary energy source for the brain. This condition can reduce their ability to concentrate during classroom learning. Purpose: To determine the relationship between breakfast habits and learning concentration among students in grades IV-VI. Method: A quantitative approach with a cross-sectional design. A total of 59 students at SDN Ujung Karang, North Lampung Regency, in 2026. The students were included as respondents using a total sampling technique. Data were collected through questionnaires assessing breakfast habits and learning concentration. The data were analyzed using univariate and bivariate analyses, with the Pearson Chi-Square test used to examine the relationship between the variables. Results: 22 respondents (37.3%) had breakfast habits in the sufficient category. Regarding learning concentration, 20 respondents (33.9%) were classified as having good concentration, while another 20 respondents (33.9%) were classified as having poor concentration. The statistical analysis obtained a p-value of 0.000 (p < 0.05), indicating a significant relationship between breakfast habits and students’ learning concentration. Conclusion: Breakfast habits were significantly associated with learning concentration among elementary school students. Regular breakfast may help provide sufficient energy and support students’ ability to concentrate during the learning process.